Observation on the Blood Composition of Cattle and Sheep in the Sudan: I. Cellular Blood Elements - Hassan, Y.M.; Holler, H. (1966)
The concentration of cellular blood elements was determined in cattle and sheep kept in Khartoum Province and in Western Sudan. The observations were made at different seasons of the year 1965/66 under varing feeding conditions. Attempt was made to find out ranges which can be regarded as normal under Sudan conditions. The R.B.C. count and haemoglobin values were usually within the normal range but on the low side. Anaemic conditions were found in animals kept at El Obeid Dairy which may be related to poor nutritional conditions. There were also signs of anaemia in sheep, probably due to underfeeding and/or parasitism. Differential counts of white blood cells revealed eosinophilia in cows and sheep which may be attributed to parasitic infestation. As far as these investigations are concerned no significant climatic influence was observed.